2004
DOI: 10.1017/s1740925x04000274
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional profiling in an MPNST-derived cell line and normal human Schwann cells

Abstract: AbstractcDNA microarrays were utilized to identify abnormally expressed genes in a malignant peripheral nerve sheath tumor (MPNST)-derived cell line, T265, by comparing the mRNA abundance profiles with that of normal human Schwann cells (nhSCs). The findings characterize the molecular phenotype of this important cell-line model of MPNSTs, and elucidate the contribution of Schwann cells in MPNSTs. In total, 4608 cDNA sequences were screened and hybridizations replicated on custom cDNA microarrays. In order to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 33 publications
2
33
0
Order By: Relevance
“…The array was constructed using a previously reported PCR-based approach for microarrays production (21,22). Briefly, genomic sequences from the 57 selected genes (Supplementary Table S2) were downloaded from Ensembl 8 (human genome build 35.1), and bioinformatic analysis was carried out using Sequence Allocator program. 9 The program combines and automates filtering out redundant stretches in the input genomic sequence and designing primers in the unique fragments.…”
Section: Methodsmentioning
confidence: 99%
“…The array was constructed using a previously reported PCR-based approach for microarrays production (21,22). Briefly, genomic sequences from the 57 selected genes (Supplementary Table S2) were downloaded from Ensembl 8 (human genome build 35.1), and bioinformatic analysis was carried out using Sequence Allocator program. 9 The program combines and automates filtering out redundant stretches in the input genomic sequence and designing primers in the unique fragments.…”
Section: Methodsmentioning
confidence: 99%
“…Hallmarks of NF1 include a range of symptoms from caf e au lait spots of the skin to tumors of the peripheral nervous system. Schwann cells (SC) have been found to be the originating cell type in most of the benign tumors (Harrisingh and Lloyd, 2004;Zhu et al, 2002) and can also contribute to malignant peripheral nerve sheath tumors (Lee et al, 2004;Miller et al, 2006). Loss of heterozygosity (LOH) is frequently seen in NF1 tumors, particularly in the SC population (Zhu et al, 2002), although not all SCs in the tumors analyzed showed LOH (Rutkowski et al, 2000;Sawada et al, 1996;Serra et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have performed cDNA microarray analysis to identify expression signatures of malignant peripheral nerve sheath tumor. 9,10,12,19 These studies have used frozen tissue or cell lines derived from tumors. They showed differences in the gene expression pattern between neurofibromas and unmatched malignant peripheral nerve sheath tumor samples from other patients.…”
mentioning
confidence: 99%